Ideological Function of Korean Painting in the Early Decades of the 20th Century (Politeja, 2025)
This paper attempts to compile the results of Korean and Western research on Korean paintings of the beginnings of the 20th century and analyze it using the theory of the ideological function of art. The main assumption is that Korean paintings of that time – their creation, as well as reception by audiences and critics – was influenced by the need to shape the national identity of Korean people and find a uniform way to represent it in art. The paper opens with an explanation of societal dimensions of art and its ideological role in particular. Attention is also given to the way art can influence shaping the national identity during times of difficulties. In later parts of the paper this identity-shaping lens is used to analyze the world of Korean painting, its main figures and their body of work, as well as the way ‘local colors’ were expressed through them.